The importance of pro-inflammatory and anti-inflammatory cytokines in Pneumocystis jirovecii pneumonia. (October 2013) - Chou, Chung-Wei; Lin, Fang-Chi; Tsai, Han-Chen; Chang, Shi-Chuan
Abstract The role of pro-inflammatory and anti-inflammatory cytokines in Pneumocystis jirovecii pneumonia (PcP) of non-AIDS immunocompromised patients remains unclear. We measured the levels of pro-inflammatory cytokines including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, IL-8, monocyte chemoattractant protein-1 (MCP-1) and anti-inflammatory cytokines including IL-10 and transforming growth factor (TGF)-β1 in bronchoalveolar lavage fluid (BALF) and blood in 36 non-AIDS immunocompromised patients with PcP diagnosed by BAL and explored their clinical importance. The severity of PcP was determined by arterial oxygen tension/fraction of inspired oxygen concentration (PaO2/FiO2) ratio, the need of mechanical ventilation and the death. Twenty-five subjects without evidence of lung abnormality were included as control group. Compared with control group, PcP patients had significantly higher BALF levels of IL-1β, TNF-α, IL-6, IL-8 and MCP-1 and significantly higher blood levels of IL-10, TGF-β1, IL-8, IL-6 and MCP-1. For PcP patients, BALF levels of IL-8, IL-8/IL-10 ratio and IL-8/TGF-β1 ratio and blood levels of IL-8 and IL-8/IL-10 ratio were significantly higher in the patients with PaO2/FiO2 < 200 mmHg than in those with PaO2/FiO2 > 200 mmHg. Similarly, significantly higher BALF levels of IL-8, IL-8/IL-10 ratio, IL-1β/IL-10, IL-1β/TGF-β1 ratio, MCP-1/TGF-β1 ratio and IL-8/TGF-β1 ratio were found in the patients requiring mechanical ventilation and in non-survivors. In summary, an imbalance of pro-inflammatory and anti-inflammatory cytokines in BALF was found in PcP of non-AIDS immunocompromised patients. BALF levels of IL-8, IL-8/IL-10 ratio, IL-1β/IL-10 ratio, IL-1β/TGF-β1 ratio, MCP-1/TGF-β1 ratio and IL-8/TGF-β1 ratio may be of value in assessing the severity of PcP and in predicting the outcome of the patients.